Late plasma exosome microRNA-21-5p depicts magnitude of reverse ventricular remodeling after early surgical repair of primary mitral valve regurgitation - Pizzino, Fausto; Furini, Giulia; Casieri, Valentina; Mariani, Massimiliano; Bianchi, Giacomo; Storti, Simona; Chiappino, Dante; Maffei, Stefano; Solinas, Marco; Aquaro, Giovanni Donato; Lionetti, Vincenzo (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Primary mitral valve regurgitation (MR) results form degeneration of mitral valve apparatus. Mechanisms leading to incomplete postoperative left ventricular (LV) reverse remodeling (Rev-Rem) despite timely and successful surgical mitral valve repair (MVR) remain unknown. Plasma exosomes (pEXOs) are smallest nanovesicles exerting early postoperative cardioprotection. We hypothesized that late exosomal microRNAs (miRs) contribute to long-term postoperative Rev-Rem. Methods: Primary MR patients (n=19; 45–71 y.o.) underwent cardiac magnetic resonance imaging and blood sampling before (T0) and six months after (T1) MVR. Postoperative LV Rev-Rem was assessed in terms of decrease in LV end-diastolic volume and patients were stratified into high (HiR-REM) and low (LoR-REM) LV Rev-Rem subgroups. Isolated pEXOs were quantified by nanoparticle tracking analysis. Exosomal microRNA (miR)-1, -21-5p, -133a, and -208a levels were measured by RT-qPCR. Anti-hypertrophic effects of pEXOs were tested in HL-1 cardiomyocytes cultured with angiotensin II (AngII, 1µM for 48h). Results: Surgery zeroed out volume regurgitation in all patients. Although preoperative pEXOs were similar in both groups, pEXO levels increased after MVR in HiR-REM patients (+0.75-fold, p=0.016), who showed lower cardiac mass index (-11%, P=0.032). Postoperative exosomal miR-21-5p values of HiR-REM patients were higher than other groups (p<0.05). In vitro, T1-pEXOs isolated from LoR-REM patients boosted the AngII-induced cardiomyocyte hypertrophy, but not postoperative exosomes of HiR-REM. This adaptive effect was counteracted by miR-21-5p inhibition. Summary/Conclusion: High levels of miR-21-5p-enriched pEXOs during the late postoperative period depict higher LV Rev-Rem after MVR. miR-21-5p-enriched pEXOs may be helpful to predict and to treat incomplete LV Rev-Rem after successful MVR